Bioteknologi Kombucha Bunga Telang Sebagai Formulasi dan Sediaan Spray dalam Menghambat Pertumbuhan Fungi Fusarium solani Penyebab Penyakit Tanaman Komoditas Hortikultura - Firman Rezaldi; Rusmana Rusmana; Susiyanti Susiyanti; Maharani Maharani; Ratu Amalia Hayani; Syariful Mubarok; Fahmie Firmansyah (Universitas Sam Ratulangi, 2023)
Based on the results of previous research, butterfly pea flower kombucha has been proven that apart from being able to be used as a probiotic drink to enhance the immune system, it can be used as an active ingredient in medicines and cosmetics, a raw material for organic liquid fertilizer, and also in formulations and spray preparations designed to inhibit the growth of pathogenic fungi that cause wilt. concave, and brownish on the stems of horticultural commodity plants. This research aims to make a fermented solution of butterfly pea flower kombucha as a formulation and spray preparation designed as an antifungal for Fusarium solani. The Fusarium solani antifungal test of each formulation and the telang flower kombucha spray preparation was carried out using disc diffusion. One-way ANOVA and post hoc analysis are the statistical analyzes used in this research. Based on the one-way ANOVA test with a p value of <0.05 each, followed by post hoc analysis, it was proven that butterfly pea flower kombucha at a sugar concentration of 40% was significantly different as an antifungal for Fusarium solani compared to 20% and 30%. The conclusion in this study is that a sugar concentration of 40% in this study is the best treatment as an antifungal for Fusarium solani, so that apart from being used as a probiotic drink, butterfly pea flower kombucha in this study has the potential to be used as an antifungal for Fusarium solani.